(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Seven months after the emergence of SARS-COV-2 virus, there is paucity of data regarding the epidemiology of the virus in hemodialysis patients. We aim to present the results of the screening program implied after outbreak of COVID-19 in a referral hemodialysis ward. Methods. We started clinical screening and obligatory mask wearing for dialysis patients and personnel on 20-Feb-2020. However 11 symptomatic COVID-19 patients emerged till day +36. On days +39 and +40 a screening program was implied including measurement of SARS-COV-2 PCR and immunoglobulin G and M (IgG/IgM) and chest computerized tomography (CCT) scan. The results of CCT scan, classified according to the coronavirus disease 2019 (COVID-19) Reporting and Data System (CO-RADS) classification; as with very low (grade 1-normal), low, indeterminate, high, and very high likelihood of COVID-19 (grades 2, 3, 4, and 5; respectively), were used for compartmentalization of patients. Results. Among 178 patients (68.2% male, mean age = 58.7 ± 16.6 years), 11 got COVID-19 before screening, two of whom died. CCT scans were normal in 71.3% and grade 2, 3, 4, and 5 in 7.9%, 4.5%, 5.6%, and 10.7%; respectively. PCR and IgG and/or IgM were positive in 27 and 32 patients. Eighty-three patients had evidence of COVID-19 infection, who were significantly older (62.2 ± 16.6 vs. 56.1 ± 16.02, P < .05). There was no difference in the rate of infection considering gender, diabetes mellitus, hypertension and different blood groups. Conclusion. Asymptomatic SARS- COV 2 infection may affect a large number of dialysis patients. We highly recommend a screening strategy whenever the number of patients is increasing.